2008
DOI: 10.1037/a0013224
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor experience affects self and emotion.

Abstract: Two studies investigated the role of locomotor experience on visual proprioception in 8-month-old infants. Visual proprioception refers to the sense of self-motion induced in a static person by patterns of optic flow. A moving room apparatus permitted displacement of an entire enclosure (except for the floor) or the side walls and ceiling. In Study 1, creeping infants and prelocomotor/walker infants showed significantly greater postural compensation and emotional responses to side wall movement than did same-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 21 publications
(29 reference statements)
3
56
1
1
Order By: Relevance
“…In such a paradigm, a third factor could contribute to the relation: Perhaps crawling infants are generally more advanced and mature than noncrawling infants. However, training studies indicate that locomotion and not a third factor leads to change in infants' visual perception (Dahl et al, 2013;Uchiyama et al, 2008). Infants who had not yet begun to crawl or walk were assigned randomly to a locomotive training (via a powered mobility device) group and a control group.…”
Section: How Are Infants' Motor Experiences Linked To Processing Objementioning
confidence: 99%
“…In such a paradigm, a third factor could contribute to the relation: Perhaps crawling infants are generally more advanced and mature than noncrawling infants. However, training studies indicate that locomotion and not a third factor leads to change in infants' visual perception (Dahl et al, 2013;Uchiyama et al, 2008). Infants who had not yet begun to crawl or walk were assigned randomly to a locomotive training (via a powered mobility device) group and a control group.…”
Section: How Are Infants' Motor Experiences Linked To Processing Objementioning
confidence: 99%
“…A number of studies have also demonstrated the relation of infant self-produced locomotor experience (through crawling or experience in an infant walker) with a broad array of psychological phenomena, including cognitive development (Bertenthal, Campos, & Barrett 1984;Bai & Bertenthal, 1992), development of spatial search (Kermoian & Campos, 1988), perceptual development (Higgins, Campos, & Kermoian, 1996), social development (Campos, Kermoian, & Zumbahlen, 1992), emotional development (Campos, Bertenthal, & Kermoian, 1992), and neurophysiological processes (Bell & Fox, 1996). Experimental studies have demonstrated that some of the above relations are caused by locomotor experience, specifically by randomly assigning prelocomotor infants to a condition in which infants control a powered-mobility device and others do not (Dahl et al, in press;Uchiyama et al, 2008). In each of these studies, the acquisition of a new motoric skill was associated with development in a broad range of psychological areas.…”
Section: Motoric Transitions As Epigenetic Phenomenamentioning
confidence: 99%
“…The onset of independent mobility is associated with the development of cognitive, perceptual, and social skills [1] [2] [3] [4]. It has even been reported that initiation of crawling is associated with physical development in an LQIDQW ¶V EUDLQ [5].…”
Section: Introductionmentioning
confidence: 99%